Meeting report: transposable elements at the crossroads of evolution, health and disease 2023 - Irina R. Arkhipova; Kathleen H. Burns; Katherine B. Chiappinelli; Edward B. Chuong; Clement Goubert; Alba Guarné; Amanda M. Larracuente; E. Alice Lee; Henry L. Levin (Mobile DNA, 2023)
Abstract The conference “Transposable Elements at the Crossroads of Evolution, Health and Disease” was hosted by Keystone Symposia in Whistler, British Columbia, Canada, on September 3–6, 2023, and was organized by Kathleen Burns, Harmit Malik and Irina Arkhipova. The central theme of the meeting was the incredible diversity of ways in which transposable elements (TEs) interact with the host, from disrupting the existing genes and pathways to creating novel gene products and expression patterns, enhancing the repertoire of host functions, and ultimately driving host evolution. The meeting was organized into six plenary sessions and two afternoon workshops with a total of 50 invited and contributed talks, two poster sessions, and a career roundtable. The topics ranged from TE roles in normal and pathological processes to restricting and harnessing TE activity based on mechanistic insights gained from genetic, structural, and biochemical studies.